A ANALYSIS OF THE EFFECT OF THE USE OF HVS PAPER WASTE ASH AS A PARTIAL SUBSTITUTION OF CEMENT ON THE COMPRESSIVE STRENGTH OF CONCRETE: ANALISIS PENGARUH PENGGUNAAN ABU LIMBAH KERTAS HVS SEBAGAI SUBTITUSI SEBAGIAN SEMEN TERHADAP KUAT TEKAN BETON - Mohammad Fiqry Teezar pratama; Ahmad yudi; Kirtinanda P (Jurnal Ilmiah Teknologi Infomasi Terapan, 2025)
This research aims to analyze the use of HVS paper ash (Hout vrij schrijfpapier) as a substitute for cement in concrete mixtures. HVS paper is one of the most widely used wastes by humans, generally used in government, private, and school agencies. This research aims to evaluate the slump value, assess the concrete compressive strength value, analyze the impact of using paper ash on concrete compressive strength using the ANOVA (Analysis of Variance) method, and study the type of cracks in each concrete sample based on ASTM C39-18 standards. The variations used were 0%, 10%, 15%, and 20% as cement substitution. The average compressive strength of each sample was 20.2 MPa, 23.3 MPa, 20.4 MPa, and 18.3 MPa, respectively. This increase occurred because paper ash has a higher silica content compared to Portland cement. However, the use of paper ash requires an activator to accelerate the mechanical properties of the paper ash itself. The activator used in this research is NaOH with a level of 4 mol. Thus, the increase in compressive strength produced by paper ash can be used as normal concrete.